Experimental Color Observation and Modelling of Drying Wasabi Leaves with Gas Heater in a Rack Dryer - Didik Iswadi; Ahmad Wibisana (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study analyzed the drying characteristics of Wasabi leaves in rack dryers with gas heating at various temperatures to obtain the most suitable thin-layer drying model while evaluating the color change and mass transfer parameters. Drying was carried out for 7.5 hours at temperatures of 60, 80, 100, and 120°C with the main variables of moisture content, moisture ratio, energy consumption, effective diffusivity, and CIE Lab* and ?E color parameters. The drying curve data were analyzed using three thin layer models (Newton, Henderson and Pabis, and Page) and evaluated with coefficients of determination (R²), chi-square (X²), and root mean square error (RMSE). The results showed that the increase in drying temperature increased specific energy consumption (9.07 × 10³ – 1.91 × 10? kJ kg?¹ water) and effective diffusivity (2.49 × 10?? – 4.11 × 10?? m² s?¹), and accelerated the reduction of moisture content to 2.27–10% at 80–120°C.   The moisture ratio is in the range of 0.02–0.98 and indicates a phase of high initial drying rate, followed by a period of decreasing rate until the weight is nearly constant around 240 minutes. The discoloration during drying was characterized by a decrease in L (13.91–42.69), an increase in a (?6.4 to 0.31), a decrease in b (11.93–24.78), and an increase in ?E (2.12–16.44), indicating a degradation of green pigment and a tendency to brown at high temperatures. Based on the R², X², and RMSE criteria, the Newton model at 60°C provides the best fit between the predictions and the experimental data, so it was chosen as the most representative model for describing the drying kinetics of Wasabi leaves in a gas rack dryer. These findings provide a quantitative database of energy, diffusivity, and colour change that can be used to optimise wasabi leaf drying operations for use as a raw material for natural dyes, thereby improving energy efficiency. Contribution to Sustainable Development Goals (SDGs): SDG 7: Affordable and Clean Energy, SDG 12: Responsible Consumption and Production; SDG 9: Industry, Innovation and Infrastructure.